Buckling Strengths of Composite Plate Using Shape Memory Alloy under In-Plane Shear - et. al., Yatendra Saraswat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, we analyze the strength and buckling response in the plane shear load fixed at the corner of the composite plate. The fem is formulated is done on the basis of first-order shear deformation theory and assumptions of von Karman. The Newton-Raphson technique is considered to analyze the non-linearity algebraic equation. The effect of shape memory alloy in shear load and buckling response is discussed. In this study we analyze the two cases in the first simple carbon/epoxy plate is analyze and then we use the shape memory wire embedded in the plate which is about 1% of the volume of the plate and studies the buckling response effect on the plate. In the second case we use Shape Memory Alloy plate and loading but a circular cutout at the middle of the plate this case we analyze for both with the use of shape memory alloy and without the use of shape memory. It is observed that the shape memory alloy increases the strength of the plate in both cases. The whole simulations are done using Ansys workbench software v 2020R2.